Evaluating The Effectiveness of Buddy Reading Strategy for Reading Comprehension in Inclusive Education - Maria Olga Jelimun (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2026)
This study examines the effectiveness of the Buddy Reading strategy in improving reading comprehension within an inclusive English classroom at SMPN 2 Langke Rembong, Manggarai. With English functioning as a global language, inclusive education requires instructional methods that support diverse learners, including students with special needs. Buddy Reading, a peer-assisted technique in which students alternate as reader and listener, is considered beneficial for promoting literacy skills, cooperation, and social interaction. A quantitative experimental design was applied involving two eighth-grade classes: an experimental group using Buddy Reading and a control group receiving conventional instruction. Both groups completed pre-tests and post-tests containing 25 multiple-choice items measuring reading comprehension. Data were analyzed using SPSS 24 through descriptive statistics, normality and homogeneity tests, and an independent samples t-test. Results showed that the experimental group achieved a higher post-test mean score (70.48) than the control group (60.51). Students with special needs in the experimental class also demonstrated clear progress. The t-test results (Sig. 0.000 < 0.05) confirmed that Buddy Reading had a significant positive impact on students’ reading comprehension. Overall, the study concludes that Buddy Reading is an effective strategy for inclusive classrooms, supporting academic improvement, vocabulary development, and positive peer interaction.